El material didáctico y su incidencia en el aprendizaje de los niños del primer año de educación básica de la escuela fiscal mixta “Alonso de Mercadillo” de la ciudad de Loja, periodo 2008-2009. Propuesta alternativa - Hidalgo Puchaicela, Ruth Marlene (2010)
In the graduate research work aims to identify how it affects the learning materials for first graders, and identify the impact of didactic material in procedural learning of children in First Year of Primary Education. It is important to note that the teaching material is a resource that provides encouragement and motivation through the circumstances that the child lives, so it is necessary to prove: if the proper management and use of materials by teachers affects learning of children and determine whether the quality of learning is related to the use thereof. To obtain the required information is used: surveys with the teachers, observation forms applied to children. In the tabulation process was used inductive - deductive, analytic - synthetic and for the development of the alternative proposal of the descriptive method. Among the main findings and conclusions of the research work it was established that. It met its stated goal, and it follows that the proper management and use of materials by the teacher affects the learning of children in the First Year Basic Education School Fiscal Mixta "Alonso's Market" in the city of Loja, academic year 2008 - 2009 Learning in children from the First Year of Basic Education, are related to the use of teaching materials by teachers, and is a major instrument in the development of the educational task as it encourages children and girls to carry out their activities generating significant learning.